(3JSgjd bQGAI GdeLSWis - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUGHF, CHh GdMSf, (B288 (3g` s
(3ChdgG (B:s
(3cJGH Cdag KGHJ Hf bQI ai JSgjd bQGAI GdeLSWi eYOd GdfgGQ gh GdOGFQI GdeYWeI GdJi JMjW HbWHi Gdadc s
(3BNQgG (B:s
(3hGYde Cf SaQ GdjghO cGf bOjekG ddSGf fbdhg Edi JTQi aGYde Pdc s
(3HgG fXGe GdJYbjHIs
(3jdi BNQ GdeNWhWI YfhGf deNWhWI JSei LOhd MQcGJ GdchGcH dGHf jhfS Ydi GdJGQjN GdaGQSis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B270s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(5 / 4642) s
Keywords: (3Gdadcs